Optimizing Portfolios Using Single Index Models and Mean-Variance From the Indonesia Stock Exchange: IDX30 - Siti Fitriyyatul Jamilah; Dwi Eko Waluyo; Amron Amron (Jurnal Telekomunikasi dan Informatika, 2024)
The purpose of the study was to determine the optimal portfolio composition using the Single Index Model and Mean-variance Model methods, then the results of the two methods were compared. Data collection was carried out using secondary data from stocks that make up the IDX30 index for the 2013-2022 period. The research method is a comparative analysis of the returns and risks obtained from the Single Index Model portfolio then compared with the return and risk of the portfolio using the Mean-variance Model with 5 portfolio combinations. The comparison is carried out by comparing the coefficient of variance of each resulting portfolio composition. The comparison is carried out by comparing the coefficient of variance of each resulting portfolio composition. The analysis results show that the portfolio produced by the Mean-Variance Model has better returns and risks than the Single Index Model.